The effect of an adhesive interaction on predicting the scratch response of PS/PPO blends. (20th May 2019) - de Bie, Vincent G.; Anderson, Patrick D.; van Breemen, Lambèrt C.A.
Abstract: Single-asperity scratching is used as a simplified contact problem to investigate the deformation due to two materials touching each other. Coupling the intrinsic polymer characteristics to the scratch response for blends of polystyrene (PS) and poly(2, 6-dimethyl-1, 4-phenylene oxide) (PPO) with varying composition is the main challenge of this study. The intrinsic deformation properties of these blends are strongly influenced by their composition. A combination of experiments and simulations is essential to understand the influence of friction on the interplay between intrinsic deformation properties and contact mechanics. Without an adhesive component in the numerical simulations, no influence of scratch velocity on the penetration depth or lateral force is observed. Furthermore, the lateral force is highly underestimated. Inclusion of an adhesive component between the indenter tip and polymer substrate results in a bow-wave in front of the sliding indenter tip. The experimentally measured lateral forces can only be predicted when the velocity-independent constant friction coefficient varies with blend composition. Therefore, knowing the intrinsic material properties, i.e. deformation kinetics and the intrinsic friction parameter, enables a quantitative prediction of the single-asperity scratch response. Graphical abstract: Image 1 Highlights: Various PS/PPO blend compositions lead to different intrinsic behavior. No trend in simulated scratch response of PS/PPO blends without adhesive interaction. Including adhesion in the simulations results in a bow wave in front of the sliding tip. A Coulomb friction model is needed for quantitative PS/PPO scratch simulations. The friction coefficient is intrinsic in nature and correlates to the PS/PPO blends.